2020
DOI: 10.1021/acsami.0c09246
|View full text |Cite
|
Sign up to set email alerts
|

Local Strain and Polarization Mapping in Ferrielectric Materials

Abstract: CuInP2S6 (CIPS) is a van der Waals material that has attracted attention because of its unusual properties. Recently, a combination of density functional theory (DFT) calculations and piezoresponse force microscopy (PFM) showed that CIPS is a uniaxial quadruple-well ferrielectric featuring two polar phases and a total of four polarization states that can be controlled by external strain. Here, we combine DFT and PFM to investigate the stress-dependent piezoelectric properties of CIPS, which have so far remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
5
16
0
Order By: Relevance
“…The histogram peaks of −25.5 pm/V and +30.5 pm/V correspond to domains of opposite polarization but are higher than the DFT predicted d values of ∼15 pm/V at zero strain . However, these peaks can be likely attributed to the LP phase as this phase is in general more often observed and the d of the HP phase is much smaller than the measured values even across a wide range of stress of several GPa . Moreover, the d of the LP phase is highly sensitive to stress and can increase strongly even for smaller stress values, and transmission electron microscopy showed that CIPS has a rich variety of topological defects that affect layer stacking and lead to local strains …”
Section: Results and Discussionmentioning
confidence: 84%
“…The histogram peaks of −25.5 pm/V and +30.5 pm/V correspond to domains of opposite polarization but are higher than the DFT predicted d values of ∼15 pm/V at zero strain . However, these peaks can be likely attributed to the LP phase as this phase is in general more often observed and the d of the HP phase is much smaller than the measured values even across a wide range of stress of several GPa . Moreover, the d of the LP phase is highly sensitive to stress and can increase strongly even for smaller stress values, and transmission electron microscopy showed that CIPS has a rich variety of topological defects that affect layer stacking and lead to local strains …”
Section: Results and Discussionmentioning
confidence: 84%
“…Below the T C , the Cu-rich CIPS domains exhibit multistate piezoelectricity, which we can observe as yellow regions in Figure a. A broad distribution of d eff (ranging from 5 pm/V to 12 pm/V) is found, which we attribute to either (1) the complex 3D domain structure inside the flake, (2) different polarization states present in the material (LP, HP), (3) distinct local strains, (4) a thickness size effect, or (5) ionic strain, which we will show in more depth below. In our analysis, we fit a single Gaussian curve to the histogram plots for each image, separating the CIPS response using a mask.…”
Section: Resultsmentioning
confidence: 89%
“…Ferroelectric field-effect transistors (6,8), negative capacitance field-effect transistors (9,10), ferroelectric tunneling junctions (1), and memristors (11) have all been demonstrated with CIPS, which are attractive for both logic and memory applications (6,12) enabling future neuromorphic computing (13)(14)(15). Besides technological potentials, CIPS is also fascinating from a materials point of view, exhibiting exotic properties such as giant negative piezoelectricity (16,17), tunable quadruple energy wells (18), large room temperature electrocaloric effect (16,19), and strong coupling between ferroelectric polarization and ionic conductivity (13,20,21). It is this coupling that motivates our current study.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmark of ferroelectricity is spontaneous polarization that can be switched by an external electric field (22,23), while in CIPS, the polarization switching is intimately coupled with ionic migration (13,20,21). This is because paraelectric-ferroelectric phase transition and polarization switching are driven by hopping of Cu ions between two equivalent positions in the S 6 octahedron of CIPS (24), and such hopping is also believed to result in the onset of ionic migration (13).…”
Section: Introductionmentioning
confidence: 99%